Primary gastric SMARCA4-deficient carcinosarcoma and sarcomatoid carcinoma: Two case reports - Zhao, Ran; Zhang, Jun jun; Zhi, Xiao; Zhang, Ren ya; Li, Lei (Frontiers in Oncology, 2025)
Gastric SMARCA4-deficient carcinosarcoma and sarcomatoid carcinoma are rare with poor prognosis. In the present study, two male patients were hospitalized due to abdominal manifestations, specifically abdominal pain and a sense of fullness and discomfort. Gastroscopic examination revealed huge raised lesions in the stomach of both individuals, subsequently leading to laparoscopic radical total gastrectomy. Histopathological analysis of surgical specimens obtained from both patients demonstrated the presence of carcinomatous and sarcomatous components. In Case 1, the sarcoma region was negative for the SMARCA4, epithelial markers cytokeratin (CK) and epithelial membrane antigen (EMA), CK, EMA, and SMARCA4 were positively expressed in the adenocarcinoma area, thereby warranting carcinosarcoma diagnosis. The sarcomatous component was identified as a tumor characterized by SMARCA4 deficiency. In Case 2, the tumor cells exhibited positive staining for CK and Vimentin, negative staining for SMARCA4, and the patient was positive for SMARCA4-deficient sarcomatoid carcinoma.